Determinant of Employee Engagement Based on Transformational Leadership, Compensation, and Work Environment at Lasmono Group in Surabaya - Zalman Alfarizt; Jojok Dwiridotjahjono (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the influence of transformational leadership, compensation, and work environment on employee engagement at Lasmono Group in Surabaya. The research was prompted by a strategic paradox within the company: despite low employee turnover rates suggesting high satisfaction, the actual level of employee engagement remained unmeasured, posing a risk of "false satisfaction." This quantitative study employed an associative causal design. The population consisted of all 120 employees at the Lasmono Group headquarters, with data collected through a saturation sampling technique. Data were gathered via questionnaires and analyzed using multiple linear regression with SPSS 26. The findings reveal that transformational leadership and work environment have a significant positive partial effect on employee engagement. However, compensation was found to have no significant partial effect. Simultaneously, all three independent variables collectively exert a significant influence on employee engagement. The coefficient of determination (Adjusted R²) indicated that 31.8% of the variance in employee engagement could be explained by these three variables, while the remainder is influenced by other factors outside the scope of this research. This study concludes that relational and psychological factors are more potent drivers of engagement than financial incentives in this specific organizational context.